On an Electron Spin Resonance Spectrometer for Quantum Information Processing - Chamilliard, Jeremy (University of Waterloo, 2011)
Electron spins are an attractive candidate for an implementation of quantum information processing (QIP) due to high polarization, fast control and long coherence times. Control in electron spin resonance beneﬁts from extensive experience in liquid-state nuclear magnetic resonance QIP, and microwave and RF technology from industry. This thesis details the design and construction of an electron spin resonance spectrometer speciﬁcally for research in quantum information processing, including the microwave electronics and variable temperature resonators and probes. We also begin to evaluate our spectrometer using a novel technique known as randomized benchmarking which extracts a ﬁgure of merit relevant to QIP.
Keywords: ESR; QIP; Physics